2020
DOI: 10.1021/acs.chemmater.9b05107
|View full text |Cite
|
Sign up to set email alerts
|

Structural Tolerance Factor Approach to Defect-Resistant I2-II-IV-X4 Semiconductor Design

Abstract: Recent work on quaternary semiconductors Cu 2 BaSn(S,Se) 4 and Ag 2 BaSnSe 4 for photovoltaic and thermoelectric applications, respectively, has shown the promise of exploring the broader family of defect-resistant I 2 -II-IV-X 4 materials (where I, II, and IV refer to the formal oxidation state of the metal cations and X is a chalcogen anion) with tetrahedrally coordinated I/IV cations and larger II cations (i.e., Sr, Ba, Pb, and Eu) for optoelectronic and energy-related applications. Chemical dissimilarity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(71 citation statements)
references
References 93 publications
6
64
0
Order By: Relevance
“…Likewise, comparisons of the calculated bandgaps for Li 2 PbGeS 4 (Aitken et al 2001) and Ag 2 PbGeS 4 (Nhalil et al, 2018;Vu et al 2018), as well as Li 2 BaGeS 4 and Ag 2 BaGeS 4 (Wu et al, 2017), further exemplify this trend (Table 5). As expected, the calculated bandgap of 2.22 eV determined for the title compound, Li 2 PbSiS 4 , is notably larger than the bandgaps of 2.13 and 0.91 eV that were calculated for the silver and copper analogs Ag 2 PbSiS 4 and Cu 2 PbSiS 4 , respectively (Sun et al, 2020;Nhalil et al, 2018) (Table 5).…”
Section: Tablesupporting
confidence: 67%
See 3 more Smart Citations
“…Likewise, comparisons of the calculated bandgaps for Li 2 PbGeS 4 (Aitken et al 2001) and Ag 2 PbGeS 4 (Nhalil et al, 2018;Vu et al 2018), as well as Li 2 BaGeS 4 and Ag 2 BaGeS 4 (Wu et al, 2017), further exemplify this trend (Table 5). As expected, the calculated bandgap of 2.22 eV determined for the title compound, Li 2 PbSiS 4 , is notably larger than the bandgaps of 2.13 and 0.91 eV that were calculated for the silver and copper analogs Ag 2 PbSiS 4 and Cu 2 PbSiS 4 , respectively (Sun et al, 2020;Nhalil et al, 2018) (Table 5).…”
Section: Tablesupporting
confidence: 67%
“…the distortion of the polyhedra causes a lowering of the symmetry from tetragonal (stannite) to orthorhombic (Teske & Vetter, 1976;Assoud et al, 2005). Additionally, there are several other related structures that can be stabilized, as explained recently by Sun and co-workers (Sun et al, 2020). For example, a number of compounds can be found in the Cu 2 SrSnS 4 structure type, crystallizing in the space group P3 1 (Teske, 1976), as well as the two different structure types with Ama2 symmetry, i.e.…”
Section: Figurementioning
confidence: 88%
See 2 more Smart Citations
“…This work is one of the pioneer studies in proposing a tolerance factor for a chalcogenide system. [52][53][54] We have also performed density functional theory (DFT) calculations to show that the cation-ordered β-KBiQ 2 polymorphs are thermodynamically stable and demonstrated that DFT can be used as a complimentary tool in the panoramic studies to determine the phase stabilities.…”
Section: Introductionmentioning
confidence: 99%